Options for Modeling Social Rational-Value Networks: Congruence Issues - Konstantin S. Kondratenko (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article introduces a new concept designed to describe the social and sociotechnical processes that were triggered by digital transformation and, in their turn, resulted in Industry 5.0. The author described and modelled egocentric, communicative, convergent, and cause-and-effect rational-semantic networks, in which rationality relies on the semantic model of the system and forms some rational concern for its values and meanings to be implemented in behavior. The theoretical side of the research could be represented as a pyramid of conceptual levels that concentrate from philosophy and general science to particular research with statistical, network, and other methods. The author introduced the term of rational-semantic system to study the network contexts of behavior, including that of social network users. The term was also applied to the phenomena and effects of network interaction, e.g. the legitimacy of network power and its effect on user behavior patterns. The methodological character of this research allows for a broader study of social and political networks. The network context revealed some congruence issues, i.e., compatibility of rational-semantic systems. The author believes that eventually all systems can be combined into a single whole.